Hippocampal mechanisms in impaired spatial learning and memory in male offspring of rats fed a low‐protein isocaloric diet in pregnancy and/or lactation. Issue 1 (14th September 2017) - Reyes‐Castro, L. A.; Padilla‐Gómez, E.; Parga‐Martínez, N. J.; Castro‐Rodríguez, D. C.; Quirarte, G. L.; Díaz‐Cintra, S.; Nathanielsz, P. W.; Zambrano, E.
Abstract: Maternal nutritional challenges during fetal and neonatal development result in developmental programming of multiple offspring organ systems including brain maturation and function. A maternal low‐protein diet during pregnancy and lactation impairs associative learning and motivation. We evaluated effects of a maternal low‐protein diet during gestation and/or lactation on male offspring spatial learning and hippocampal neural structure. Control mothers (C) ate 20% casein and restricted mothers (R) 10% casein, providing four groups: CC, RR, CR, and RC (first letter pregnancy, second lactation diet). We evaluated the behavior of young adult male offspring around postnatal day 110. Corticosterone and ACTH were measured. Males were tested for 2 days in the Morris water maze (MWM). Stratum lucidum mossy fiber (MF) area, total and spine type in basal dendrites of stratum oriens in the hippocampal CA3 field were measured. Corticosterone and ACTH were higher in RR vs. CC. In the MWM acquisition test CC offspring required two, RC three, and CR seven sessions to learn the maze. RR did not learn in eight trials. In a retention test 24 h later, RR, CR, and RC spent more time locating the platform and performed fewer target zone entries than CC. RR and RC offspring spent less time in the target zone than CC. MF area, total, and thin spines were lower in RR, CR, and RC than CC. Mushroom spines were lower in RR and RC than CC. Stubby spines were higher in RR, CR, and RC than CC. We conclude that maternal low‐protein diet impairs spatial acquisition and memory retention in male offspring, and that alterations in hippocampal presynaptic (MF), postsynaptic (spines) elements and higher glucocorticoid levels are potential mechanisms to explain these learning and memory deficits.